The outcome of severe varicella pneumonia with respiratory failure admitted to the intensive care unit for mechanical ventilation. Issue 1 (5th July 2018) - John, Kiran George; John, Thadathilankal-Jess; Taljaard, Jantjie J.; Lalla, Usha; Esterhuizen, Tonya M.; Irusen, Elvis M.; Koegelenberg, Coenraad F.N.
Varicella pneumonia carries a mortality of 10–30%; mortality rate increases to 50% in patients that warrant mechanical ventilation secondary to respiratory failure despite appropriate antiviral and supportive treatment. Risk factors for the development of severe disease include cigarette smoking, pregnancy, immunocompromised states and more extensive skin involvement [1]. Treatment options for life-threatening varicella consist mainly of cardiorespiratory support, antiviral therapy and steroid use. The benefit of antiviral therapy, however, is still controversial [2]. Varicella pneumonia still carries a high mortality rate (29.2% in this study). Metabolic acidosis, a higher APACHE II score and the presence of acute renal failure on admission predicted poor outcome. http://ow.ly/CdQM30jAY5q